Peran Pengelolahan Keuangan Sekolah : Transparansi dan Akuntabilitas Kepada Masyarakat - Mohammad Ramadona (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the role of transparency in managing school finances. The method used is the method of qualitative research methodology. Research procedures that produce descriptive data in the form of words written or spoken from people and behavior that can be seen. This research is a single case study because researchers only conduct research at SMK Al Hadid 2 Bogor. Transparency and accountability in school financial statements largely determine the quality of the school. The more transparent and accountable, the school will be able to be trusted, and get full support from school stakeholders. Accountability and transparency of Alhadid 2 vocational school is good enough The more transparent and accountable a financial report is, the public trust can be improved. However, improvements and improvements in management need to be improved, so that it can run well. The result indicates that the acuntabilities has 76 score. It mean good enough. The school can improve the quality of school.